POLA PRODUKSI SPERMATOZOA KELELAWAR MIKROCHIROPTERA (Rhinolophus stheno) DI GUA INDARUNG PADANG - Kasmeri, Ria (Sainstek : Jurnal Sains dan Teknologi, 2011)
Research about Sperm Production Pattern of Lesser Brown Horseshoe bat (Rhinolophus stheno): Microchiroptera in Indarung cave, Padang had. This research was using descriptive method toward testes preparation of Lesser Brown Horseshoe bat with using Hematoxilin-Eosin staining to observe the presence of spermatozoa. The result showed that the spermatogenesis activity on January until April 2007 was inactive, because there was no spermatozoa and seminiferous tubules epithelium only consisted of spermatogonium and spermatocytes. Spermatogenesis activity was started on May and spermatozoa had been released on June. R. stheno follows the bimmodally polyestrus reproduction pattern based on the hypothetical diagram that constructed as supporting mean for this statement.Key words: sperm production, lesser brown horseshoe bat